Asymptotic formulas for integer partitions within the approach of microcanonical ensemble - Prokhorov, D.; Rovenchak, A. (Condensed Matter Physics, 2012)
The problem of integer partitions is addressed using the microcanonical approach which is based on the analogy between this problem in the number theory and the calculation of microstates of a many-boson system. For ordinary (one-dimensional) partitions, the correction to the leading asymptotic is obtained. The estimate for the number of two-dimensional (plane) partitions coincides with known asymptotic results. Розглянуто задачу про розбиття цiлих чисел у межах мiкроканонiчного пiдходу, який ґрунтується на аналогiї мiж цiєю задачею з теорiї чисел i обчисленням кiлькостi мiкростанiв багатобозонної системи. Для звичайних (одновимiрних) розбиттiв отримано поправку до головної асимптотики. Оцiнка кiлькостi двовимiрних (плоских) розбиттiв добре узгоджується з вiдомими асимптотичними результатами.